ChemInform Abstract: A Synthesis of 1H‐Indazoles via a Cu(OAc)2‐Catalyzed N—N Bond Formation. Issue 32 (22nd July 2016) - Chen, Cheng‐yi; Tang, Guangrong; He, Fengxian; Wang, Zhaobin; Jing, Hailin; Faessler, Roger
Abstract: A variety of 1H‐indazoles is readily prepared by reaction of nitriles (I) with Grignard reagents followed by a copper‐catalyzed oxidative cyclization of intermediate ketimines.